Continuous production of stretchable conductive multifilaments in kilometer scale enables facile knitting of wearable strain sensing textiles. (June 2018) - Seyedin, Shayan; Moradi, Sepehr; Singh, Charanpreet; Razal, Joselito M.
Graphical abstract: Highlights: A kilometer-scale spinning of conductive elastomeric multifilaments is demonstrated. Multifilaments are knitted into strain sensing textiles with various patterns. Strain sensing behavior can be tuned by varying loop configuration and stitch insertion. Knitted textiles can be worn directly on various body parts to track their movements. Abstract: A facile large scale production of conductive and elastomeric fibers can enable the fabrication of functional fabrics for diverse applications including sensing for wearable and industrial textiles. Strain sensing textiles are gaining particular attention because of their increasing relevance in the development of smart devices for health, sports, and soft robotics. Current approaches to make sensing textiles rely on mounting a sensor or coating a sensing material onto existing fabrics. Here, we demonstrate the production of conductive elastomeric multifilaments in kilometer scale, which enables the facile knitting of textile prototypes that can detect large strains (up to 200%) with high stability (up to 500 cyclic stretching). Five different knit prototypes are fabricated to demonstrate that strain sensing behavior can be tailored using simple alterations in the loop configurations and stitch insertions in the knit structures. Strain sensing textiles that can be worn directly on various body parts ( i.e. knee, elbow, and finger) without the need for any supporting structures or frames and can monitor diverse movements such as bending and kicking are demonstrated. This work provides scalable approaches for the fabrication of conductive elastomeric fibers and textiles that can be used for a wide range of sensing applications.